Mad men. Season six [videorecording (DVD)]. - Hamm, Jon, 1971-; Paré, Jessica; Moss, Elisabeth, 1982- (Lionsgate, 2013)
Returning for its sixth season, Mad Men explores the glamorous and ego-driven 'golden age' of advertising in late 1960s New York City. Don Draper and the rest of the cast continue to captivate as they deal with the aftereffects of adultery, divorce, a merger, and an ever-changing social climate.